A rare case of obstructed lumbar hernia: case report - Rathod, Ankit; Banerjee, Divya Jyoti; Panchal, Hemang; Mehta, Urja (International Journal of Research in Medical Sciences, 2024)
Lumbar hernias are quite uncommon as compared to other ventral abdominal wall hernias, accounting for less than 1.5% of all abdominal hernias, with fewer than 300 cases reported over the past 300 years. About 25% of all lumbar hernias have a traumatic etiology. This may be post-surgical or following blunt injuries associated with intra-abdominal injuries. The management of such patients constitutes a surgical challenge. Clinical diagnosis of this entity is difficult due to non-specific symptoms. The diagnosis is particularly elusive in obese individuals or in post-surgical patients. Though rare defects, lumbar hernias are prone to incarceration and strangulation. CECT will provide valuable insight into diagnosis of lumbar hernia especially if obstructed or strangulated. Here we present a case report of a rare presentation of obstructed lumbar hernia diagnosed with CT scan and managed with exploratory laparotomy.